On Certain Class of Analytic Functions Related to Cho-Kwon-Srivastava Operator - F. Ghanim; M. Darus (International Journal of Mathematics and Mathematical Sciences)
Motivated by a multiplier transformation and some subclasses of meromorphic functions which were defined by means of the Hadamard product of the Cho-Kwon-Srivastava operator, we define here a similar transformation by means of the Ghanim and Darus operator. A class related to this transformation will be introduced and the properties will be discussed.